Revegetation of subtropical soil slopes: Groundcover performance and the implications of urban development and slope features on plant community. Issue 4 (19th July 2018) - Chau, Ngai Lung; Chu, Lee Man
Abstract: Questions: Is revegetation of soil slopes with the currently used plant groundcovers effective in promoting dense vegetation and ecological values of landscapes? Does the degree of urban development influence the abundance of groundcovers? Is there any relationship between slope features and the plant community of soil slopes? Location: Hong Kong Special Administrative Region, China. Methods: We conducted a vegetation study focusing on groundcovers on 35 revegetated soil slopes in urban and suburban areas of Hong Kong and determined differences in plant cover, diversity and community composition among areas under various degrees of development. We also assessed slope features, including presence of erosion control mats, canopy openness, slopes angle, area, elevation and substrate properties, such as soil pH, electrical conductivity (EC) and nutrient status, to examine their relationships to the plant community composition. Results: Plant cover was generally about 30%, with ferns having the highest cover. The initially planted groundcover species were replaced by native graminoids and ferns, or an invasive climbing herb, Wedelia trilobata . Soil slopes covered by erosion control mats had significantly lower plant cover than those without. Contrasting plant community composition of groundcovers was found among areas with different degrees of urban development and between slopes with and without erosion control mats. Slope angle, canopy openness, sandy soil texture and soil EC were closely associated with the plant communities of soil slopes. Conclusions: The current planted groundcovers used for revegetating soil slopes led to unsatisfactory plant cover but allowed colonization of other native groundcovers. Planting strategy using more adaptable native groundcovers, but not invasive species, is a feasible approach to ecologically restore soil slopes. The degree of development and certain slope features influence the plant community and should be considered in the revegetation of soil slopes. Abstract : This study evaluated the growth performance and ecological enhancement of groundcovers on revegetated soil slopes in Hong Kong. This is a topic that receives little attention. Our results show that naturally occurring ferns and graminoids dominate the landscapes, although their cover percentage was generally low. The presence of erosion control mats and some slope features influence plant community composition of revegetated soil slopes.